Tinjauan Literatur Tentang Etika Pemasaran Syariah: Prinsip, Implementasi, Dan Tantangan Dalam Bisnis Modern - Ambarwati, Diana; Abroza, Ahmad (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Sharia showcasing morals has ended up an vital subject in cutting edge trade as mindfulness of moral standards in financial exercises proceeds to develop. Sharia promoting centers on the application of Islamic values in showcasing hones, such as equity, straightforwardness, and social duty. This ponder points to supply a comprehensive writing audit on the standards of Sharia promoting morals, its execution in commerce hones, and the challenges companies confront when applying these concepts within the digital period. The investigate strategy utilized may be a subjective writing audit, analyzing 50 pertinent diaries and insightful books. These sources incorporate distributions from 2018 to 2023, centering on Sharia showcasing and Islamic trade practices.The study's discoveries appear that the most standards of Sharia showcasing incorporate trustworthiness (91%), straightforwardness (87%), and adjusting the interface of makers and buyers (82%). In terms of execution, around 75% of companies applying Sharia showcasing techniques detailed an increment in client devotion, whereas 68% of companies experienced feasible commerce development. Be that as it may, the most challenges confronted are the integration of innovation in Sharia promoting (65%) and competition with non-Sharia companies (58%). In conclusion, Sharia promoting can be an successful technique for building customer believe and guaranteeing trade maintainability. Be that as it may, way better adjustment to present day innovation and worldwide showcase challenges is required.